Exploring the Relationship Between Financial Literacy and Financial Capability Among Micro, Small, and Medium Enterprises in Kupang City - Yuri S. Fa'ah; Dominikus Kopong T. Aman (CV. Vocezmi Learnov, 2025)
The Micro, Small, and Medium Enterprises (MSME) sector in Kupang City has experienced substantial growth in recent years and has increasingly become a central pillar supporting regional economic development. Despite this progress, numerous studies consistently indicate that MSME actors continue to face significant challenges in managing their business finances, including unsystematic record-keeping, insufficient budgeting practices, and limited access to formal financial services. These persistent constraints often result in restricted working capital, unstable cash flows, and reduced business resilience in responding to market dynamics. In response to these issues, this study aims to examine the relationship between the core dimensions of financial literacy—namely financial behavior, financial attitudes, financial knowledge, and financial capability—among MSME actors in Kupang City. Drawing on the active MSME population in 2022, a final sample of 173 respondents was selected using the Slovin formula, and data were gathered through a structured questionnaire survey. Multiple regression analysis, conducted using SPSS version 25, was employed to assess the extent to which each dimension of financial literacy influences financial capability. The findings demonstrate that financial behavior and financial attitudes exert a positive and statistically significant effect on financial capability, while financial knowledge shows a more varied and less consistent relationship. These results underscore the need for financial education initiatives that not only enhance cognitive understanding but also foster sound financial behaviors and attitudes. Furthermore, the study highlights the importance of comprehensive MSME empowerment strategies aimed at strengthening financial resilience and promoting long-term business sustainability in Kupang City.